A three-dimensional MXene film aerogel and preparation method thereof
By controlling the foaming time and temperature, the MXene film is accurately regulated and the pore structure is introduced between the layers, and alkali metal ion preintercalation layer and amino modification are introduced to form a three-dimensional MXene film aerogel with high electrochemical properties and mechanical stability, which solves the problem of low electrochemical properties of MXene materials.
Patent Information
- Application Number
- CN202410949457.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-07-16
AI Technical Summary
Due to the strong van der Waals interaction, MXene nanosheets are prone to aggregation and self-stack to form dense structures, resulting in low electrochemical performance, and the pore structure of the aerogel cannot be accurately regulated and poor structural integrity.
By controlling the foaming time and temperature, the MXene film is accurately regulated, and a three-dimensional MXene film aerogel with a porous network structure is formed, and an alkali metal ion preintercalation layer and amino modification are introduced between the layers to form a Na+ preintercalation layer and amino modified three-dimensional MXene film aerogel.
The precise regulation of the pore structure of MXene films is achieved, the electrochemical performance is enhanced, the mechanical stability is improved, and the layer spacing is expanded, solving the problem of low specific capacity of MXene materials.
Smart Images

Figure CN118908213B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal carbide materials and aerogel functional material preparation processes, and more specifically to an alkali metal ion pre-intercalation and amino-modified three-dimensional MXene thin film aerogel electrode material, a preparation method thereof, and electrochemical energy storage applications. Background Art
[0002] Flexible supercapacitors have important applications in wearable electronic products due to their advantages such as high capacitance, long cycle life, low cost and flexibility. Electrode materials have a great influence on the electrochemical properties of capacitors and flexible energy storage devices. Ideal flexible electrode materials should have the characteristics of high conductivity, moderate pore size, interconnected pore structure and good mechanical flexibility.
[0003] MXene is a type of 2D transition metal carbon / nitride material with a general chemical formula of M n+1 X n T x (n=1,2,3), where M represents a transition metal element, X represents C, T x Represents the terminal functional group (-OH, -F, -O, etc.). MXenes have adjustable terminal groups, large specific surface area, high theoretical capacity and energy density, unique hydrophilicity and good mechanical flexibility, and have great potential as flexible electrode materials for supercapacitors. However, due to the strong van der Waals interaction, MXene nanosheets are prone to aggregation and self-stacking to form a dense structure, which leads to low ion transport efficiency between MXene nanosheets and inactivation of electrochemical active sites, thereby reducing their electrochemical performance.
[0004] Aerogels have the advantages of being conducive to electrolyte penetration, shortening ion diffusion distance, and resisting electrode expansion and contraction stress in the field of energy storage. However, aerogels currently have problems such as the inability to precisely control the pore structure and poor structural integrity.
[0005] In order to solve the above problems, the present invention proposes an alkali metal ion pre-intercalation and amino-modified three-dimensional MXene thin film aerogel electrode material, a preparation method thereof, and electrochemical energy storage applications.
[0006] Therefore, this patent not only proposes a method to accurately adjust the pore structure of thin film aerogels, but also provides a method to change the terminal groups of MXene, reveals the mechanism of interlayer spacing and Na+ pre-intercalation, and also demonstrates the broad application prospects of thin film aerogels in wearable power sources. Summary of the invention
[0007] The purpose of the present invention is to propose an alkali metal ion pre-intercalation and amino-modified three-dimensional MXene film aerogel electrode material and its preparation method and electrochemical energy storage application to solve the problems raised in the background technology. The present invention precisely regulates the pore structure of the MXene film by controlling the foaming time and temperature, and converts the MXene film into an aerogel with a porous network structure without losing its mechanical properties, while further protecting the application of the prepared three-dimensional MXene film aerogel in supercapacitors for electrochemical energy storage.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A method for preparing a three-dimensional MXene thin film aerogel comprises the following steps:
[0010] S1. Ti 3 AlC 2 and LiF were added to HCl and etched in a water bath;
[0011] S2. The etched powder is washed several times with deionized water until it becomes neutral to form multilayer MXene;
[0012] S3, intercalating the multilayer MXene flakes obtained in S2 with dimethyl sulfoxide to obtain the final few-layer MXene flakes;
[0013] S4, the solution in S3 was filtered to form a film, and then directly freeze-dried to obtain a flexible film. The obtained sample was named Ti 3 C 2 film;
[0014] S5, the Ti obtained in S4 3 C 2 Film in N 2 H 4 Heat in a water bath to foam and form pores to form a 3D thin film aerogel;
[0015] S6, introducing alkali metal ions into the few-layer MXene flakes, stirring, and preparing alkali metal ion pre-intercalated MXene nanosheets;
[0016] S7, filtering the alkali metal ion pre-intercalated MXene nanosheets obtained in S6 into a thin film using a vacuum pump;
[0017] S8. The film obtained in S7 is heated to N 2 H 4 The foaming is carried out by heating in a water bath to form pores, and finally a 3D thin film aerogel with alkali metal ions pre-intercalated is formed.
[0018] Preferably, Ti in S1 3 AlC 2The mass ratio of LiF to HCl is 3-5:1, the volume of HCl is 70-90 mL, the water bath temperature is 40-60° C., and the time is 48 h.
[0019] Preferably, the deionized water washing in S2 is performed 3 to 5 times until the pH value reaches 7.
[0020] Preferably, the volume of dimethyl sulfoxide in S3 is 70-90 mL, and the stirring treatment time is 12 h.
[0021] Preferably, the volume of the solution used for the suction filtration and membrane formation in S4 is 15 to 25 mL.
[0022] Preferably, N in S5 2 H 4 The concentration is 50%, the water bath foaming temperature is 30℃, 50℃, and 70℃, and the heating time is 48h.
[0023] Preferably, the S6 specifically includes the following contents:
[0024] Add 5-15 mmol of a metal salt containing an alkali metal ion to 15-25 mL of a few-layer MXene sheet and stir for 4 hours to obtain an alkali metal ion pre-intercalated MXene nanosheet;
[0025] The alkali metal ions include but are not limited to Li + 、Na + and K + .
[0026] Preferably, N in S8 2 H 4 The concentration is 50%, the water bath foaming temperature is 30℃, 50℃, and 70℃, and the heating time is 48h.
[0027] The alkali metal ion pre-intercalation and amino-modified three-dimensional MXene thin film aerogel prepared by the above method.
[0028] Application of the above three-dimensional MXene thin film aerogel in supercapacitors for electrochemical energy storage.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention proposes a method for preparing an alkali metal ion pre-intercalation and amino-modified three-dimensional MXene thin film aerogel electrode material, wherein NaCl is spontaneously inserted into the MXene interlayer to form a Na + Then generate Na + Pre-intercalated Ti 3 C 2 (Na-Ti 3 C 2). Then filter and form a membrane, and the Na-Ti 3 C 2 In N 2 H 4 The solution was foamed and pore-formed at 50 °C and the terminal groups were modified to obtain the sample Na-Ti 3 C 2 T x Among them, N 2 H 4 The decomposed bubbles generate ordered pores between the two-dimensional MXene sheets, forming a 3D network-like thin film aerogel. The MXene sheets overlap each other to form an interlocking topological structure, which enhances the interaction between the interfaces and makes the Na-Ti 3 C 2 T x The sheet has superb mechanical stability and can resist extreme deformation. The foaming rate can be controlled by temperature, which can also achieve Ti 3 C 2 T x Fine control of interlayer transport channel structure and interface.
[0031] (2) The present invention adopts N 2 H 4 Foaming successfully doped N and Ti 3 C 2 Some terminal groups -NH 2 In addition, N 2 H 4 The ratio of reduced -F and -OH groups decreases due to the additional formation of -NH 2 Group, and replaces part of the terminal group. 2 This changes the electronic structure of the material and improves its conductivity.
[0032] In summary, the present invention precisely regulates the pore structure of the MXene film by controlling the foaming time and temperature, and converts the MXene film into an aerogel with a porous network structure without losing its mechanical properties. The mesopores and macropores generated in the interconnected layered skeleton of the MXene film aerogel can serve as an electrolyte buffer reservoir, promote the shuttle of electrolyte ions, and enable ions to pass through the channel with little resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is an overall flow chart of a method for preparing a three-dimensional MXene thin film aerogel proposed in the present invention;
[0034] Figure 2 is (a)Ti mentioned in Example 1 of the present invention 3 C 2 (b) Ti 3 C2 T x -30, (c) Ti 3 C 2 T x -50, (d) Ti 3 C 2 T x -70 and (e)Na-Ti 3 C 2 T x -50 thin film aerogel cross section SEM image, (f) Na-Ti 3 C 2 T x -50 Optical photos of thin film aerogel;
[0035] Figure 3 is the Ti mentioned in Example 1 of the present invention 3 AlC 2 、Ti 3 C 2 、Ti 3 C 2 T x -30, Ti 3 C 2 T x -50, Ti 3 C 2 T x -70 and Na-Ti 3 C 2 T x -50's XRD pattern;
[0036] Figure 4 is the Ti mentioned in Example 1 of the present invention 3 C 2 and Ti 3 C 2 T x -50 infrared spectrum;
[0037] Figure 5 is the Ti mentioned in Example 1 of the present invention 3 C 2 、Ti 3 C 2 T x -50 and Na-Ti 3 C 2 T x (a) Nitrogen adsorption-desorption isotherm and (b) pore size distribution diagram of -50;
[0038] Figure 6 is the Ti mentioned in Example 1 of the present invention 3 C 2 、Ti 3 C2 T x -30, Ti 3 C 2 T x -50, Ti 3 C 2 T x -70 and Na-Ti 3 C 2 T x -50 (a) mass specific capacity and (b) area specific capacity at different current densities;
[0039] Figure 7 The Na-Ti mentioned in Example 1 of the present invention 3 C 2 T x -50 cycle performance curve at a current density of 10A / g;
[0040] Figure 8 is the Ti mentioned in Example 1 of the present invention 3 C 2 、Ti 3 C 2 T x -50 and Na-Ti 3 C 2 T x -50 and commercial AC assembled into asymmetric flexible devices (a) mass (b) volume energy density and power density relationship;
[0041] Fig. 9 The Na-Ti mentioned in Example 1 of the present invention 3 C 2 T x -50 / / AC cycle performance curve at current density of 6A / g. DETAILED DESCRIPTION
[0042] The technical solution and its effects of the present invention are further described below in conjunction with specific implementation modes / examples. The following implementation modes / examples are only used to illustrate the content of the present invention, and the present invention is not limited to the following implementation modes or examples.
[0043] The present invention proposes a three-dimensional MXene thin film aerogel and a preparation method thereof. First, the Li + 、Na + and K +Plasma is inserted between the MXene layers to adjust the interlayer spacing. Secondly, the redox reaction is affected by controlling the type and content of the terminal groups on the MXene surface. The present invention further protects the aerogel material prepared by the above method and the application of the material in high-performance supercapacitors and the assembly of flexible asymmetric supercapacitor devices. Please refer to Figure 1 , including the following:
[0044] (1) Ti 3 AlC 2 and LiF were added to HCl and etched in a water bath;
[0045] (2) The etched powder was washed several times with deionized water until the pH was 7 to form multilayer MXene;
[0046] (3) intercalating the multilayer MXene flakes with dimethyl sulfoxide to obtain the final few-layer MXene flakes;
[0047] (4) filtering the few-layer MXene nanosheets obtained in step (3) into a thin film using a vacuum pump;
[0048] (5) The film obtained in step (4) was subjected to 30-80% N 2 H 4 The pores are formed by foaming in a water bath at 30-70°C to eventually form a 3D thin film aerogel.
[0049] The present invention provides a method for preparing an alkali metal ion pre-intercalated MXene thin film aerogel material, which expands the interlayer spacing of the MXene material and solves the problem of low specific capacity of the MXene material.
[0050] In one embodiment, the few-layer MXene nanosheets obtained in step (3) are prepared by electrostatic self-assembly using metal salts to form alkali metal ions (Li + 、Na + and K + ) pre-intercalated MXene nanosheets;
[0051] In one embodiment, the alkali metal ion (Li + 、Na + and K + ) pre-intercalated MXene nanosheets are filtered into thin films using a vacuum pump, and then alkali metal ions (Li + 、Na + and K + )Pre-intercalated 3DMXene thin film aerogel.
[0052] The present invention further utilizes the aforementioned N 2 H 4Foaming and pore formation changes the number and type of terminal groups of MXene and forms N element doping, which solves the problems of low specific capacity and poor stability of MXene aerogel.
[0053] In one embodiment, the Na + Pre-intercalated MXene film aerogel electrode material at 0.5MH 2 SO 4 The specific capacity (at 1A / g) is 200-600F / g, for example, Ti 3 C 2 、Ti 3 C 2 T x -30, Ti 3 C 2 T x -50, Ti 3 C 2 T x -70 and Na-Ti 3 C 2 T x The specific capacities of -50 are 258F / g, 312F / g, 363F / g, 417F / g and 560F / g respectively.
[0054] Furthermore, the present invention further comprises Na + Pre-intercalated MXene thin film aerogel is directly used as electrode and combined with activated carbon to form a flexible asymmetric device, which solves the problem of low energy density of MXene materials.
[0055] In one embodiment, the Na-Ti 3 C 2 T x -50 / / AC has an energy density of 52.8Wh / kg (1600W / kg). (AC stands for activated carbon)
[0056] The following is a description of a three-dimensional MXene thin film aerogel and a preparation method thereof proposed in the present invention in combination with specific examples and related drawings:
[0057] Example 1
[0058] (1) 4g Ti 3 AlC 2 and 1gLiF were added to 80mL HCl, 60℃ / 48h water bath;
[0059] (2) The etched powder is washed with deionized water several times until it becomes neutral to form multilayer MXene;
[0060] (3) Multilayer MXene flakes were added into 80 mL of dimethyl sulfoxide and stirred for 12 h to obtain the final few-layer MXene flakes;
[0061] (4) The few-layer Ti obtained in step (3) 3 C 2 The solution was filtered to form a film, and then directly freeze-dried to obtain a flexible Ti 3 C 2 Thin film; (sample named Ti 3 C 2 )
[0062] (5) The film obtained in step (4) was added to 20 mL of 50% N 2 H 4 The solution was heated at 30℃, 50℃, and 70℃ for 48h to form pores in a water bath, and finally a 3D thin film aerogel was formed. 3 C 2 T x -30, Ti 3 C 2 T x -50 and Ti 3 C 2 T x -70)
[0063] (6) 10 mmol NaCl was added to 20 mL of few-layer MXene flakes and stirred for 4 h to prepare Na + Pre-intercalated MXene nanosheets; (the concentration of few-layer MXene flakes is 13 mg / mL)
[0064] (7) The Na obtained in step (6) + The pre-intercalated MXene nanosheets are filtered into a thin film using a vacuum pump;
[0065] (8) The film obtained in step (7) was added to 20 mL of 50% N 2 H 4 The solution was heated at 50°C for 48 hours in a water bath to form pores, and finally Na + Pre-intercalated 3D thin film aerogel. (named Na-Ti 3 C 2 T x -50)
[0066] The prepared aerogel material was tested and characterized, and the specific contents are as follows:
[0067] See also Figure 2 , Figure 2 In the present invention, (a) Ti 3 C 2 (b) Ti 3 C2 T x -30, (c) Ti 3 C 2 T x -50, (d) Ti 3 C 2 T x -70 and (e)Na-Ti 3 C 2 T x -50 thin film aerogel cross section SEM image, (f) Na-Ti 3 C 2 T x Optical photograph of -50 thin film aerogel.
[0068] Depend on Figure 2 It can be seen that N 2 H 4 By creating bubbles between the two-dimensional material layers to form a 3D network-like structure, MXene sheets overlap each other to form an interlocking topology, which enhances the interaction between the interfaces and enables Ti 3 C 2 T x The sheets have great mechanical stability and are resistant to extreme deformation. 3 C 2 The SEM image of Ti shows an irregularly arranged lamellar structure. 3 C 2 T x -30, Ti 3 C 2 T x -50, Ti 3 C 2 T x -70 N 2 H 2 After foaming and pore formation, it presents a 3D network structure with different thicknesses (30℃-300um, 50℃-400um, 70℃-400um), and Ti 3 C 2 T x -30, (c) Ti 3 C 2 T x -50, (d) Ti 3 C 2 T x -70 and Na-Ti 3 C 2 T x -50 (thickness 400um) has a more ordered network structure, which is conducive to exposing more active sites. 3 C 2 T xThe optical photograph of -50 further proves the successful transformation of the MXene film into a three-dimensional structure.
[0069] Figure 3 Ti 3 AlC 2 、Ti 3 C 2 、Ti 3 C 2 T x -30, Ti 3 C 2 T x -50, Ti 3 C 2 T x -70 and Na-Ti 3 C 2 T x -50's XRD pattern.
[0070] From the XRD pattern, we can see that after etching, Ti 3 AlC 2 The (002) peak of the MAX phase shifts to a lower angle, and the Ti 3 C 2 There are six main peaks (i.e., (002), (004), (006), (008), (0010), and (0012)), indicating that MXene was successfully synthesized. 3 C 2 The interlayer spacing is 1.35nm. 2 H 2 After foaming and reduction, Ti 3 C 2 T x -30, Ti 3 C 2 T x -50 and Ti 3 C 2 T x -70 (002) crystal plane interlayer spacing narrows (1.31, 1.34, 1.25nm respectively), which is because different temperatures lead to N 2 H 2 The different foaming rates and the changes in the surface groups of MXene lead to the narrowing of the interlayer spacing. 3 C 2 T x -50 has an interlayer spacing of 1.42nm, which is much larger than Ti 3 C 2 and Ti 3 C 2 T x -50, indicating that the Na ion pre-intercalation was successful.
[0071] Figure 4 Ti 3 C 2 and Ti 3 C 2 T x -50's infrared spectrum.
[0072] From the infrared spectrum, we can see that at 1090 and 557 cm -1 There are two peaks at , which are due to the surface terminal groups of CF and -OH. 3 C 2 T x -50 spectrum at ~1400cm -1 The peak at corresponds to CN, confirming that N 2 H 4 The reduction leads to N-doping of MXene.
[0073] Figure 5 Ti 3 C 2 、Ti 3 C 2 T x -50 and Na-Ti 3 C 2 T x (a) Nitrogen adsorption-desorption isotherm and (b) pore size distribution of -50.
[0074] Depend on Figure 5 It can be seen that Ti 3 C 2 、Ti 3 C 2 T x -50 and Na-Ti 3 C 2 T x The specific surface areas of -50 are 12.5, 30.6, and 45.2 m 2 g -1 , indicating that N 2 H 4 Foaming reduction and Na + Pre-intercalation effectively increases the specific surface area of the material. 3 C 2 (8.63nm and 14.76nm), Ti 3 C 2 T x -50and Na-Ti 3 C 2 T x The micropore size of -50 is 1.36nm, the mesopore size is 6.34nm and 8.63nm, and the macropore size is 147.6nm, indicating that N 2H 4 The foaming can produce micropores and some mesopores. The material has a micropore-mesopore-macroporous structure, and the porous structure can accelerate the adsorption and rapid transfer of ions during the charge and discharge process.
[0075] Table 1Ti 3 C 2 、Ti 3 C 2 T x -30, Ti 3 C 2 T x -50, Ti 3 C 2 T x -70 and Na-Ti 3 C 2 T x -50 specific surface area and pore structure parameters
[0076]
[0077] From Table 1, we can see that N 2 H 4 Heating foaming to form pores will increase the micropore content, and the micropore content is higher at 50℃, so 50℃ is N 2 H 4 The best temperature for foaming. 3 C 2 T x -50 has the highest micropore content, indicating that Na + Pre-intercalation helps to form micropores.
[0078] Table 2Ti 3 C 2 、Ti 3 C 2 T x -50 and Na-Ti 3 C 2 T x -50 terminal group concentration (%)
[0079]
[0080] From Table 2, we can see that N 2 H 4 After reduction, the proportion of C-Ti-Fx and C-Ti-(OH)x decreased from 33.60% to 27.20%, and the proportion of C-Ti-(OH)x decreased from 50.90% to 38.30%, which is due to the 2 Additional formation of groups and substitution of some hydroxyl groups.
[0081] Figure 6 Ti3 C 2 、Ti 3 C 2 T x -30, Ti 3 C 2 T x -50, Ti 3 C 2 T x -70 and Na-Ti 3 C 2 T x (a) gravimetric capacity and (b) area-specific capacity of -50 at different current densities.
[0082] As can be seen from the figure, Na-Ti 3 C 2 T x -50 has the highest specific capacity, reaching 560F / g at 1A / g.
[0083] Figure 7 Na-Ti 3 C 2 T x -50 cycle performance curve at a current density of 10A / g.
[0084] The results showed that Na-Ti 3 C 2 T x -50 exhibits ultra-high cycling stability after 12,000 cycles, and the specific capacitance only drops to 95.45% after 12,000 cycles.
[0085] Figure 8 Ti 3 C 2 、Ti 3 C 2 T x -50 and Na-Ti 3 C 2 T x Relationship between (a) mass and (b) volumetric energy density and power density of an asymmetric flexible device assembled with -50 and commercial AC.
[0086] According to calculations, the flexible device Na-Ti 3 C 2 T x -50 / / AC has a mass energy density of 52.8Wh / kg at a power density of 1600W / kg and a volume energy density of 37.76Wh / L at 1142.3W / L.
[0087] Fig. 9 Na-Ti 3 C2 T x -50 / / AC cycle performance curve at current density of 6A / g.
[0088] The results showed that Na-Ti 3 C 2 T x -50 / / AC showed good stability after 10,000 cycles, with a capacity retention rate of 61.1%.
[0089] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and improved concepts of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a three-dimensional MXene thin film aerogel, characterized in that: The following steps are involved: S1, adding Ti3AlC2 and LiF into HCl, and etching in a water bath; the mass ratio of Ti3AlC2 and LiF is 3-5:1, the volume of HCl is 70-90 mL, and the water bath temperature is 40-60 o C, time is 48 h; S2. The etched powder is washed with deionized water for several times until it is neutral to form multilayer MXene; the number of times of deionized water washing is 3 to 5 times until pH = 7; S3, intercalating the multilayer MXene flakes obtained in S2 with dimethyl sulfoxide to obtain the final few-layer MXene flakes; S4, the solution in S3 is filtered to form a film, and directly freeze-dried to obtain a flexible film. The obtained sample is named Ti3C2 film; S5, heating the Ti3C2 film obtained in S4 in a N2H4 water bath to foam and form pores to form a 3D thin film aerogel; S6, introducing alkali metal ions into the few-layer MXene flakes, stirring, and preparing alkali metal ion pre-intercalated MXene nanosheets; S7, filtering the alkali metal ion pre-intercalated MXene nanosheets obtained in S6 into a thin film using a vacuum pump; S8. The film obtained in S7 is heated in a water bath in N2H4 to foam and form pores, and finally a 3D thin film aerogel with alkali metal ion pre-intercalation is formed.
2. The method for preparing the three-dimensional MXene thin film aerogel according to claim 1, characterized in that: The volume of dimethyl sulfoxide in S3 is 70-90 mL, and the stirring treatment time is 12 h.
3. The method for preparing the three-dimensional MXene thin film aerogel according to claim 1, characterized in that: The volume of solution used for filtration and membrane formation in S4 is 15~25 mL.
4. The method for preparing the three-dimensional MXene thin film aerogel according to claim 1, characterized in that: The concentration of N2H4 in S5 is 50%, the water bath foaming temperatures are 30°C, 50°C, and 70°C, and the heating time is 48 h.
5. The method for preparing the three-dimensional MXene thin film aerogel according to claim 1, characterized in that: The S6 specifically includes the following contents: Add 5-15 mmol of metal salt containing alkali metal ions into 15-25 mL of few-layer MXene sheets and stir for 4 h to obtain alkali metal ion pre-intercalated MXene nanosheets; The alkali metal ions include but are not limited to Li + 、Na + and K + .
6. The method for preparing the three-dimensional MXene thin film aerogel according to claim 1, characterized in that: The concentration of N2H4 in S8 is 50%, the water bath foaming temperatures are 30°C, 50°C, and 70°C, and the heating time is 48 h.
7. Alkali metal ion pre-intercalation and amino-modified three-dimensional MXene thin film aerogel prepared by the method described in any one of claims 1 to 6.
8. Application of the three-dimensional MXene thin film aerogel as claimed in claim 7 in supercapacitors for electrochemical energy storage.
Citation Information
Patent Citations
Preparation method of three-dimensional porous flexible self-supporting film electrode material
CN118156060A